Bike sharing systems data interoperability by a unified station status concept and big data solutions - Francisco Márquez-Saldaña; Gonzalo A. Aranda-Corral; Joaquín Borrego-Díaz (Journal of Traffic and Transportation Engineering (English ed. Online))
The impact of bike sharing systems (BSS) on urban mobility, and their study as part of the overall transport system in smart cities, has attracted significant academic interest in recent years. However, the lack of historical and standardized data in current service tools hinders the analysis and improvement of these platforms, i.e. by reusing technical data-based solutions. Big data nature (in volume, variety and velocity) of collecting BSS historical information must be also addressed, in order to take an integrated perspective.This paper describes an integrated solution to this challenge by (1) proposing a unified station status concept for recording historical information, based on the identification, study and unification of common relevant fields found in almost all BSS data warehouses, and (2) implementing a big data-inspired ETL infrastructure together with a storage optimization, methodology which not only allows to access and collect previous defined concepts but also overcomes existing big data challenge when storing BSS information. The system also consumes other external relevant information, such as weather factors, which have been aggregated, enhancing stored knowledge, with KPIs and statistics. The developed solution illustrates how it can manage over seven years of data from twenty-seven BSS, serving not only machine-to-machine communication but also human-computer communication and enabling data-driven solutions.